Multiplatform Journalism dan Transformasi Media Lokal: Konvergensi Harian Ambon Ekspres sebagai Strategi Komunikasi Adaptif - Jaha, Samuel; Rumra, Fatmawati; Salakay, Selvianus (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to analyze the adaptive communication strategies employed by Harian Ambon Ekspres through a multiplatform journalism approach in response to the transformation of local media in the digital era. Utilizing a qualitative method with a case study approach, data were collected through observation, in-depth interviews, and document analysis focused on media convergence practices at Harian Ambon Ekspres. The findings reveal that the main strategies include content diversification through the production of radio podcasts, which are subsequently disseminated across both print and digital formats; the use of various digital media platforms to expand audience reach and engagement; and the integration of four key platforms: the Harian Ambon Ekspres print newspaper, E-Paper, Ambonterkini.id, and Ameks.fajar.co.id. Moreover, media convergence has proven effective in reducing production costs and strengthening the competitiveness of the media institution amid technological disruption. The novelty of this study lies in its revelation that convergence functions not only as a technological adaptation but also as a cultural communication strategy that enables local media to remain relevant to the evolving needs and preferences of the public. These findings contribute significantly to the fields of social and political sciences, particularly in media studies, communication, and digital cultural dynamics, and highlight the importance of enhancing the innovation capacity of local media in navigating an ever-changing communication landscape.